Commodity prices, money and inflation - Frank Browne; David Cronin (European Central Bank (ECB), 2007)
The influence of commodity prices on consumer prices is usually seen as originating in commodity markets. We argue, however, that long run and short run relationships should exist between commodity prices, consumer prices and money and that the influence of commodity prices on consumer prices occurs through a money-driven overshooting of commodity prices being corrected over time. Using a cointegrating VAR framework and US data, our empirical findings are supportive of these relationships, with both commodity and consumer prices proportional to the money supply in the long run, commodity prices initially overshooting their new equilibrium values in response to a money supply shock, and the deviation of commodity prices from their equilibrium values having explanatory power for subsequent consumer price inflation.
Keywords: E31; E51; E52; 330; impulse response analysis; overshooting; VECM; Rohstoffpreis; Verbraucherpreisindex; Inflation; Geldpolitik; Theorie; USA